SOSIALISASI PENGEMBANGAN SIKAP SOSIAL MELALUI CERITA LOKAL SASAK TK NURUL IKHLAS DESA AIK MUAL KECAMATAN PERAYA LOMBOK TENGAH - Mujtahidin, Samsul; Muzdalifah, Fithrii; Muhibbin, Muhibbin (INSANTA : JURNAL PENGABDIAN KEPADA MASYARAKAT, 2023)
The general problems in this Community Service are: First: there is still a lack of understanding among parents regarding the development of social attitudes through local Sasak stories, Second: there is a lack of ideas for parents about developing social attitudes through local Sasak stories so that many children's social attitudes are not developed enough, Third: the large number of people Parents still don't know the importance of developing social attitudes, so many parents pay little attention to developing children's social attitudes. In terms of developing social attitudes through local Sasak stories in children, it is not as easy as you imagine because you have to consider aspects starting from planning the selection of themes for local Sasak stories in developing social attitudes in children, storytelling methods to attract children's attention so they want to listen to the story, and heat. so that children don't get bored easily. In this activity parents, teachers and students are given an understanding of the importance of developing social attitudes to support children's growth and development